Heterotopic Pregnancy: a Case Report - Khanom, Mst Nazmun Nahar; Das, Sanjoy Kumar; Akter, Nitol; Tasnim, Sohana (Faridpur Medical College Journal, 2025)
Heterotopic pregnancy is defined as the coexistence of intrauterine and extra uterine gestation. The incidence is rare and estimated to be 1 in 30,000 of spontaneous pregnancies though it is becoming commoner with assisted reproductive technique. It can be a life threatening condition and can be easily missed with the diagnosis being overlooked. We present a rare case of spontaneous heterotopic pregnancy composed of missed abortion and ruptured left adnexal gestation. Faridpur Med. Coll. J. 2025;20(2):57-59